Aplikasi Digital Marketing Pelaku Usaha Kecil dan Menengah Komunitas Gedebage Market - Iwan Rijayana; Sri Lestari; Murnawan Murnawan; Ucu Nugraha; Rae Virgana; Rosalin Samihardjo (Jurnal PkM (Pengabdian kepada Masyarakat), 2023)
As many as 33% of Small and Medium Enterprises (SMEs) in Gedebage Bandung District are SMEs that produce their own products, while the rest are resellers. The products sold are of various types consisting of various products such as: food, drinks, clothes, sandals, shoes to rattan handicrafts. The outbreak of the Covid-19 disease in Indonesia resulted in many business people experiencing losses. This is also felt by SMEs who are members of the Gedebage Market community. To overcome the problems caused by the Covid-19 pandemic, a good effort is needed to be able to manage business activities so that they are able to overcome the economic crisis they are experiencing. Digital marketing is widely used by business people around the world. Digital marketing is an alternative that is suitable for SMEs. The selected business partners are reseller partners who are productive economic groups, so that community empowerment programs related to the implementation of digital marketing can run well, partners are given digital marketing training. The activities started with a preliminary survey, socialization, making digital marketing training materials, checking training materials, implementing training on making digital marketing applications, guidance, mentoring, monitoring and evaluation. The mandatory output achieved is the publication of digital marketing applications on electronic media